Nutritional Status and Infant Feeding Practices Adopted by Working Women in Jodhpur City - Fotedar, Ranjana; Lakshminarayana, J; Ramanath, T; Singh, Madhu B (Annals of Arid Zone, 2016)
A survey was conducted on 200 working women from urban area inJodhpur, mainly to assess their health and nutritional status. Majority of the womenreported that working outside home was mainly to improve their living standard.Thirty seven women were from well-to-do families, 52 from Middle Income Group(MIG) and I I I were from Low Income Group (LIG). A large family size andlow literacy were found associated with LIG when chi-square test was applied.A significantly low percentage (P) of women were found discarding colostrumsin well-to-do group (16.1 %) as compared to MIG (56.1 %) and LIG (59.3%). Delayedsupplementation beyond I year was observed for LIG (39.8%), as compared toMIG (12.1 %) and well-to-do (6.5%) families. Similarly, longer duration of breastfeeding was seen in women of LIG. Well-to-do women opted for commercial food(55.0%) and had better awareness of supplemental food for infants. while the rest'opted for traditional food foLsupplementation. A significantly higher percentage(30.5%) of malnutrition (BMI